Do negative childhood conditions increase the risk of somatic symptoms in adolescence? - a prospective cohort study - Trine N. Winding; Johan H. Andersen (BMC, 2019)
Abstract Background In order to prevent health and social problems later in life, it is important to identify childhood conditions related to the development of somatic symptoms. This prospective study expands on previous research by investigating whether negative childhood conditions are related to somatization later in life, taking other risk factors into account. This study aims to investigate whether somatic symptoms of the participants' parents, poor family functioning, or negative life events during childhood result in somatic symptoms in early or late adolescence. Methods The study population includes participants from the West Jutland Cohort Study who responded to the survey on their somatic symptoms at age 15 (n = 2963) and/or age 18 (n = 2341). The study also includes additional questionnaire information about the participants' poor family functioning, number of negative life events, and parental reports of somatic symptoms as well as register information about parental socioeconomic background. Generalized linear models for the binomial family were used and the results were presented as relative risks (RR) and risk differences (RD) with 95% confidence intervals (95%-CI). Results Experiencing poor family functioning at age 15 showed associations with somatic symptoms at age 15 (RR 1.75, 95%-CI, 1.43-2.14 and RD 18, 95%-CI, 11-25%) and 18 (RR 1.32, 95%-CI, 1.00-1.75 and RD 7, 95%-CI, 0.2-14%). The relative risks between poor family functioning and somatic symptoms were 2.5 for the boys at age 15 and 1.71 for the girls at age 18. Having experienced two or more negative life events up to the age of 15 was associated with reporting somatic symptoms at age 15 (RR 1.73, 95%-CI, 1.31-2.28 and RD 24, 95%-CI, 11-37%). No relative risks above 1.35 were found between parents reporting somatic symptoms and participants reporting somatic symptoms at ages 15 or 18. Conclusions An increased awareness of the association between a poor social climate in the family and somatic symptoms may help professionals in health and educational systems prevent the development of such symptoms among adolescents.